Veto of New York buprenorphine PA bill angers advocates. Issue 2 (10th January 2020) - Knopf, Alison
Abstract : New York Governor Andrew Cuomo's veto on Jan. 1 of a bill that would have removed prior‐authorization barriers for all formulations of buprenorphine in the Medicaid program was greeted with dismay by the Legal Action Center and others who had fought hard for it. He did, however, sign a similar bill that removed prior‐authorization buprenorphine barriers for commercial insurance. So, it is only the poor who will be adversely affected.